DETEKSI DINI KASUS ADHD MENGGUNAKAN METODE PLAY THERAPY EXERCISE DI POSYANDU BALITA CEMPAKA IV SUDIROPRAJAN - Darmastuti, Ferina Agustin; Fatikhasari, Berliana; Alhamdaniyah, Bunga Asri; Prasasti, Nurlisa; mahendra, Yanuar Danu; Setiawan, Cahyo; Ramadhani, Alinda Nur (Universitas Sanata Dharma, 2024)
Attention Deficit Hyperactivity Disorder (ADHD) is described as a developmental disorder characterized by symptoms of inattention, hyperactivity, and impulsivity. ADHD can be classified into three subtypes depending on the intensity of symptoms: inattention dominant, hyperactive-impulsive dominant, and combined. Preschool age, also known as early childhood, is the age when growth patterns develop rapidly. The golden period is when children younger than six years old acquire excellent skills, such as perception, interaction, and speaking. During this period, children learn to process information quickly, become reliable models, become smarter and smarter than what they see, and form the basis for the formation of their attitudes and knowledge. The study was conducted with the parents of Posyandu Balita Cempaka 4 Sudiroprajan members as the participants. Based on the pretest and posttest analysis, it could be seen that after health education about early detection in children, the parents' knowledge increased. In addition, play therapy methods were used to prevent cases of ADHD in children, reducing the case rate from 10% to 100% good knowledge.